The Effect of Product Quality, Service Quality on Customer Loyalty Mediated Satisfaction for Grabfood Customers in Jabodetabek - Sahid, Wahno; Abadi, Feryyal (International Journal of Science and Society, 2024)
Customer loyalty is a crucial factor in an organization's growth and financial performance. This study aims to investigate how Product Quality influences customer loyalty, service quality, and customer happiness among Grab Food’s customers while making purchases. The population for this study consists of all online Grab food consumers in Indonesia, with a sample size of 173 online Grab food clients. The research used Structural Equation Models (SEM) for data analysis.). Research shows that both product quality and service quality have a significant influence on Grab Food’s customer loyalty in the Jabodetabek area. This shows that aspects such as food taste, ease of ordering, and speed of delivery contribute significantly to customers' decisions to continue using Grab Food services repeatedly. Mediating Role of Customer Satisfaction: The research results also highlight the important role of customer satisfaction as a mediator between product quality/service and customer loyalty. Important managerial implications for Grab Food. highlighting the importance of Grab Food’s focus on improving their Product Quality and services. Companies can carry out a thorough evaluation of the production process and service provision to ensure that the products and services provided meet customer expectations.